Budaya Organisasi, Motivasi, dan Kompetensi Karyawan dalam Perspektif Nilai-Nilai Islam: Studi Empiris pada Perbankan Indonesia - Riyan Syahdarma; Maswanto; Muhammad Yusuf (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2025)
This study aims to analyze the effect of organizational culture, motivation, and competence on employee performance and to examine its implications from the perspective of Islamic economics and business. Human resources represent a strategic factor in the development of financial institutions, including the banking sector, which in Islamic economic thought are viewed not merely as production inputs but as a trust (amanah) that must be managed professionally and in accordance with Islamic values. This research employs a quantitative associative approach. Primary data were collected through questionnaires distributed to 94 employees of PT. Bank Rakyat Indonesia, Jakarta City Branch. Multiple linear regression analysis was applied as the data analysis technique. The results indicate that organizational culture and competence have a positive and significant effect on employee performance, while motivation has a positive but insignificant effect. Simultaneously, organizational culture, motivation, and competence significantly influence employee performance. These findings suggest that a strong organizational culture and high competence are consistent with the Islamic principles of amanah and itqan, which emphasize professionalism, responsibility, and excellence in work. Meanwhile, the insignificant effect of motivation implies that material-based motivation alone is insufficient to enhance optimal performance without the internalization of spiritual motivation, such as perceiving work as an act of worship and orienting efforts toward falah (holistic well-being). This study contributes conceptually to the development of human resource management within the framework of Islamic economics and business by highlighting the importance of organizational culture and employee competence as key drivers of sustainable performance in the banking sector.